Relation between bradycardia dependent long QT syndrome and QT prolongation by disopyramide in humans. Issue 1 (1st January 1998) - Furushima, Hiroshi; Niwano, Shinichi; Chinushi, Masaomi; Ohhira, Kouji; Abe, Akira; Aizawa, Yoshifusa
Abstract : Background: Recent molecular biological investigations have identified abnormal genes in familial forms of long QT syndrome, but in bradycardia dependent acquired long QT syndrome, no such genetic abnormality has yet been identified. Objective: To investigate the relation between the responses of QT interval to pacing change and to disopyramide. Methods: This study included 13 patients with bradyarrhythmia who had undergone pacemaker implantation. The patients were divided into two groups: group I (n = 8), patients with QT prolongation (QT interval ⩾ 500 ms) during bradycardia; group II (n = 5), patients without QT prolongation (QT interval < 500 ms) during bradycardia. The responses of QT interval caused by the change of pacing rate were determined and compared with the changes of the QT interval after disopyramide administration. Results: The QT interval in group I was significantly longer than that in group II when the pacing rate was decreased from 110 to 50 beats/min: mean (SD) 451 (16) v 416 (17) ms at 90 beats/min (p = 0.0033), and 490 (19) v 432 (18) ms at 70 beats/min (p = 0.0002), respectively. The QT interval was prolonged significantly by disopyramide in both groups, but the change was more pronounced in group I than in group II: 78 (33) v 35 (10) ms (p < 0.05). Conclusions: This study suggests that the patients showing bradycardia dependent QT prolongation are also more markedly affected by disopyramide and that abnormal potassium channel may be the underlying mechanism.